2014
DOI: 10.1016/j.yhbeh.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in salivary estradiol predict changes in women's preferences for vocal masculinity

Abstract: 22Although many studies have reported that women's preferences for masculine 23 physical characteristics in men change systematically during the menstrual cycle, the 24 hormonal mechanisms underpinning these changes are currently poorly understood. 25Previous studies investigating the relationships between measured hormone levels and 26women's masculinity preferences tested only judgments of men's facial 27 attractiveness. Results of these studies suggested that preferences for masculine 28 characteristics in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 49 publications
(4 reference statements)
2
34
5
1
Order By: Relevance
“…In contrast to our findings, a recent study found that within-subject changes in estradiol predicted women’s preferences for vocal masculinity in men’s voices [20]. This apparent sex difference in hormonal modulation of voice preferences may potentially reflect overall differences in mating strategies, as women may use more and finer-grained information about potential mates, or may be more sensitive to cues of quality, in order to offset potentially greater costs to their fitness associated with poor partner choice [32].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to our findings, a recent study found that within-subject changes in estradiol predicted women’s preferences for vocal masculinity in men’s voices [20]. This apparent sex difference in hormonal modulation of voice preferences may potentially reflect overall differences in mating strategies, as women may use more and finer-grained information about potential mates, or may be more sensitive to cues of quality, in order to offset potentially greater costs to their fitness associated with poor partner choice [32].…”
Section: Discussioncontrasting
confidence: 99%
“…Following other recent work on perceptions of sexually dimorphic vocal characteristics (e.g., [20]), we created two feminized and two masculinized versions of each original voice recording by independently manipulating voice pitch or formants using the Pitch-Synchronous Overlap Add (PSOLA) algorithm in Praat version 5.2.15 [21]. Pitch was raised (feminized) or lowered (masculinized) by 10% from baseline while holding formants constant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each participant completed five consecutive weekly test sessions. Data on 45 of these women's voice preferences are reported in Pisanski et al (2014). Data on the reward value of adult facial attractiveness and infant facial cuteness for 39 and 45 of these women are reported in Wang et al (2014) and Hahn et al (2015), respectively.…”
Section: Participantsmentioning
confidence: 99%